GATE 2019 Mechanical Engineering: previous year solved questions(1991-2018) - Kreatryx (KREATRYX Pub., 2018)
GATE 2019 Mechanical Engineering: previous year solved questions(1991-2018) / Kreatryx. -- New Delhi: KREATRYX Pub., 2018 153.94621 K92 No. of Copies : 5